Accounting for product impact in the oil and gas industry - Panella, Katie,Serafeim, George,Trinh, Katie (Harvard Business School, 2021)
We apply the product impact measurement framework of the Impact-Weighted Accounts Initiative (IWAI) in two competitor companies within the oil and gas industry. We design a monetization methodology that allows us to calculate monetary product impact estimates of natural gas provision to emerging markets, energy provided, and emissions created. Our results indicate differences in the impact that competitors have through their products. These differences demonstrate how impact reflects corporate strategy and informs decision-making on industry-specific areas
10.2139/ssrn.3877518
Keywords: Graue Literatur; Product Innovation; Impact; Impact Investing; Impact Measurement; ESG; ESG (Environmental; Social; Governance) Performance; ESG Ratings; Social Corporate Responsibility; Corporate Social Responsibility; Social Impact; Oil; Oil ＆ Gas; Oil And Gas; IWAI; Product Design; Product Positioning; Society; Environmental Sustainability; Corporate Social Responsibility and Impact; Product